TRANSLATION SHIFTS OF NOUN PHRASES IN STUDENTS’ NARRATIVE TEXT - Yurike Suhertian Poyungi; Dessy Dwijayatanti (JR-ELT (Journal of Research in English Language Teaching), 2026)
This study aims to investigate the types of translations shifts occuring in noun phrases within students’ narative texts, as well as to identify the most dominant shift categories. This study also focuses on describing how students modify noun phrase structures when translating meaning between Source Language (SL) and Target Language (TL). Furthermore, this study employed a descriptive qualitative method. Data were collected through purposive sampling and  involved 20 students of Midfery students at Kusuma Husada University. Then, data were analyzed by content analysis, using classification of translation shifts frameworks. The findings reveal that structure shifts are the most dominant types of translations shifts in students’ narrative texts, followed by class shift. The discussion also indicates that translation shifts do not reduce meaning of accuracy; rather than they contribute to greater naturalness, accuracy, and readability in translation. This study offers a focused and systemic analysis of noun phrase translation shifts in students’ narrative texts. It also contributes to advance existing knowledge by revealing how translation shifts are necessary strategies to maintain equvalence, clarity, naturalness in Target Language (TL).